Elevated auxin and reduced cytokinin contents in rootstocks improve their performance and grafting success. Issue 12 (16th May 2017) - Li, Wei; Fang, Chu; Krishnan, Sanalkumar; Chen, Junmei; Yu, Hao; Murphy, Angus S.; Merewitz, Emily; Katin‐Grazzini, Lorenzo; McAvoy, Richard J.; Deng, Ziniu; Zale, Janice; Li, Yi
Summary: Plant grafting is an important technique for horticultural and silvicultural production. However, many rootstock plants suffer from undesirable lateral bud outgrowth, low grafting success rates or poor rooting. Here, we used a root‐predominant gene promoter ( SbUGT ) to drive the expression of a tryptophan‐2‐monooxygenase gene ( iaaM ) from Agrobacterium tumefaciens to increase auxin levels in tobacco. The transgenic plants, when used as a rootstock, displayed inhibited lateral bud outgrowth, enhanced grafting success rate and improved root initiation. However, root elongation and biomass of SbUGT::iaaM transgenic plants were reduced compared to those of wild‐type plants. In contrast, when we used this same promoter to drive CKX (a cytokinin degradation gene) expression, the transgenic tobacco plants displayed enhanced root elongation and biomass. We then made crosses between the SbUGT::CKX and SbUGT::iaaM transgenic plants. We observed that overexpression of the CKX gene neutralized the negative effects of auxin overproduction on root elongation. Also, the simultaneous expression of both the iaaM and CKX genes in rootstock did not disrupt normal growth and developmental patterns in wild‐type scions. Our results demonstrate that expression of both the iaaM and CKX genes predominantly in roots of rootstock inhibits lateral bud release from rootstock, improves grafting success rates and enhances root initiation and biomass.